Analisis Pengukuran Kinerja di Departement Quality PT. ABC Dengan Metode Balance Score Card dan Path Analysis - Kenny Halim; Ryan Permana; Andi Setyawan; Zulfa Fitri Ikatrinasari (JURNAL TEKNIK INDUSTRI, 2019)
To achieve the company's vision and mission as well as the strategy needed by strategic targets (strategy map) from each department to be able to match the indicators that can be obtained from each department. In this study conducted at the quality department at PT. ABC by using a balance perspective 4 score card. Balance Score Card is one of the management tools used to carry out strategies and measure performance with 4 factor perspectives. Key performance indicators (KPI) will be included in the annual performance appraisal and the KPI assessment results will be carried out with controls and reviews with a certain time frequency. The results of the analysis increase the performance and motivation of employees towards improving employee performance by increasing employee performance with a significance of 0,000 <0,05, while the work motivation of employees in improving employee performance by increasing employee performance with a significance of 0,030 <0,05.